Appraisal of Attitudes and Utilizations of Information and Communication Technology (ICT) Among Students in Nigerian Universities - Abdulhamid, Mustapha; Dauda, Sufiyanu (Universitas Terbuka, 2019)
The study examined the attitude and utilization of information and communication technology among university students. The study adopted descriptive Ã¢â‚¬â€œ survey as its design, and a population of one thousand three hundred and seventy seven (1377) students were used for the study out of which three hundred and two (302) were purposively sampled from the Department of Science and Vocational Education of the Faculty of Education and Extension Services, Usmanu Danfodiyo University, Sokoto. Two research instruments were used StudentsÃ¢â‚¬â„¢ attitude towards Information and Communication Technology (SAICT) and Information and Communication Technology utilization (ICTU). The instruments were pilot tested using Cronbach alpha and reliability index of 0.93 and 0.77 were obtained. The research found that students have positive attitude towards ICT, it was also found that students utilize ICT for academic purpose, and that students attitude is related to utilization. The study recommends that Science education students should be encouraged by the university to sustain their positive attitude towards ICT by ensuring that the students have easy access to the facilities at every point in time.Ã‚Â Ã‚Â